Ismeretlen olvasónők - Kucserka, Zsófia (Studia Litteraria, 2014)
Short stories and novels written by Zsigmond Kemény in the 1850’s are usually known as female readings, intended mainly for women. These stories are often studied focusing on female characters or on the author’s biography (and the role that a woman played in it). The present study is on female readings: examining two examples of how women read and interpreted novels and how they could express their opinions. Firstly, it studies a critique by Pál Gyulai (1854), who has a debate with a countess in his writing. The question under debate is how a female character can be interpreted. After explaining this critique, the second example is a monography from 1903, written by one of the first Hungarian literary women, Irma Langheim. In her book, Langheim studies the female characters of Zsigmond Kemény, and she finds them full of life. These examined that female interpretations seemed to be important steps of literary history as history of readings.